2019
DOI: 10.31901/24566330.2019/19.01.683
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico Target Prediction for Hsa-Mir-27a and Identification of Genes Involved In Breast Cancer

Abstract: The aim was to evaluate the impact of ABCB1 polymorphisms, C1236T and G2677T/A on the incidence of depression, its progression and effectiveness of antidepressant treatment in Polish population. Analyses were performed in 92 patients with recurrent depressive disorder (rDD) using automated sequencing. The obtained data were correlated with the results for C3435T polymorphism published earlier. Following that, a haplotype analysis was performed. For G2677T/A, the severity of depressive symptoms was higher among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These targeted miRNAs are important regulators involved in the development and metastasis of breast cancer that are mainly associated with the change in expression of PCK1 and LPL. Additionally, has-miR-27a-3p is a two-sided regulator of the transformation of metabolism and metastasis [19]. Evidence has shown that it can reduce the expression of PCK1, which is an essential enzyme in gluconeogenesis, and shift the metabolism toward favoring cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These targeted miRNAs are important regulators involved in the development and metastasis of breast cancer that are mainly associated with the change in expression of PCK1 and LPL. Additionally, has-miR-27a-3p is a two-sided regulator of the transformation of metabolism and metastasis [19]. Evidence has shown that it can reduce the expression of PCK1, which is an essential enzyme in gluconeogenesis, and shift the metabolism toward favoring cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These targeted miRNA are important regulators involved in the development and metastasis of breast cancer that are mainly associated with the change in expression of PCK1 and LPL. Additionally, has-miR-27a-3p has been found to be a two-sided regulator of transformation of metabolism and metastasis [10]. Evidence has shown that it can reduce the expression of PCK1, which is an essential enzyme in gluconeogenesis and shift the metabolism toward favoring cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%